Polishing composition, polishing method, and method for producing semiconductor substrate

The polishing composition, featuring silica particles with specific electrical conductivity and pH levels, effectively polishes both polycrystalline silicon and silicon oxide films at high speeds with a high selectivity ratio, addressing the need for improved manufacturing efficiency.

JP7663386B2Active Publication Date: 2025-04-16FUJIMI INCORPORATED
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021049533
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-24
Publication Date
2025-04-16
Estimated Expiration
2041-03-24

AI Technical Summary

Technical Problem

There is a need for a polishing composition that can efficiently polish both polycrystalline silicon films and silicon oxide films at high speeds while maintaining a high selectivity ratio of the polishing rate of the polycrystalline silicon film.

Method used

A polishing composition containing abrasive grains with a silanol group density of 0/nm² to 4 pcs/nm², silica particles with electrical conductivity between 0.5 mS/cm and 10 mS/cm, and a pH of 10 to 12, which allows for effective polishing of both polycrystalline silicon and silicon oxide films.

Benefits of technology

The polishing composition achieves a high polishing rate for both polycrystalline silicon and silicon oxide films while maintaining a high selectivity ratio of the polishing rate of the polycrystalline silicon film, enhancing manufacturing productivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007663386000001
    Figure 0007663386000001
  • Figure 0007663386000002
    Figure 0007663386000002
Patent Text Reader

Abstract

To provide polishing composition which allows a polycrystal silicon film and a silicon oxide film to be polished at a high polishing rate and which is high in selection ratio of the polishing rate of the polycrystal silicon film.SOLUTION: A polishing composition comprises: abrasive grains; an alkali compound; and a dispersion medium. The abrasive grains contains silica particles of which the silanol group density is over 0 / nm2 and no more than 4 / nm2. The polishing composition has an electric conductivity of 0.5 mS / cm or more and 10 mS / cm or less, and it is no less than pH10 and no more than pH12.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing composition, a polishing method, and a method for producing a semiconductor substrate. [Background technology]

[0002] In recent years, new microfabrication technologies have been developed to accompany the high integration and high performance of LSI (Large Scale Integration). Chemical mechanical polishing (CMP) is one of these technologies, and is frequently used in the LSI manufacturing process, especially in the multi-layer wiring formation process, for planarizing interlayer insulating films, forming metal plugs, and forming buried wiring (damascene wiring).

[0003] CMP has been applied to each process in semiconductor manufacturing, and one aspect of this is its application to the gate formation process in transistor fabrication. When fabricating a transistor, materials such as metal, silicon, silicon oxide, polycrystalline silicon, and silicon nitride film may be polished, and there is a demand for polishing each material at high speed to improve productivity. In order to meet such a demand, for example, Patent Document 1 discloses a technology that aims to improve the polishing speed of polycrystalline silicon. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2013-041992 A Summary of the Invention [Problem to be solved by the invention]

[0005] While studying the application of CMP to each process in semiconductor manufacturing, the present inventors discovered that in some cases, it is preferable in terms of manufacturing to polish not only polycrystalline silicon films but also silicon oxide films at high speed, and that in such cases, it is preferable in terms of manufacturing to have a high ratio of the polishing rate of the polycrystalline silicon film to the polishing rate of the silicon oxide film (hereinafter also referred to as the "selectivity of the polishing rate of the polycrystalline silicon film"). However, little research has been done on this new finding so far.

[0006] Therefore, the problem to be solved by the present invention is to provide a polishing composition capable of polishing polycrystalline silicon films and silicon oxide films at a high polishing rate and having a high selectivity for the polishing rate of the polycrystalline silicon film. [Means for solving the problem]

[0007] In order to solve the above problems, the present inventors have conducted extensive research. As a result, a polishing composition containing an abrasive, an alkaline compound, and a dispersion medium, in which the abrasive has a silanol group density of 0 / nm 2 More than 4 pieces / nm 2 The present inventors have found that the above problem can be solved by a polishing composition containing silica particles having an electrical conductivity of 0.5 mS / cm or more and 10 mS / cm or less and a pH of 10 or more and 12 or less, and have thus completed the present invention. Effect of the Invention

[0008] According to the present invention, there is provided a polishing composition which is capable of polishing a polycrystalline silicon film and a silicon oxide film at a high polishing rate and has a high selectivity for the polishing rate of the polycrystalline silicon film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described, but the present invention is not limited to only the following embodiments. Unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (20 to 25°C) and relative humidity 40 to 50% RH. In addition, in this specification, "X to Y" indicating a range means "X or more and Y or less."

[0010] <Polishing composition> The present invention relates to a polishing composition used for polishing an object to be polished, the polishing composition comprising an abrasive grain, an alkaline compound, and a dispersion medium, the abrasive grain having a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 The polishing composition of the present invention contains silica particles having a pH of 0.5 to 10 mS / cm, has an electrical conductivity of 0.5 to 10 mS / cm, and has a pH of 10 to 12. The polishing composition of the present invention having such a configuration is capable of polishing a polycrystalline silicon film and a silicon oxide film at a high polishing rate, and has a high selectivity for the polishing rate of the polycrystalline silicon film (the ratio of the polishing rate of the polycrystalline silicon film to the polishing rate of the silicon oxide film).

[0011] The reason why the polishing composition of the present invention exhibits the above-mentioned effects is not necessarily clear, but is thought to be as follows. However, it goes without saying that the following mechanism is merely speculation and does not limit the technical scope of the present invention.

[0012] A polishing composition generally polishes an object to be polished by a physical action caused by rubbing the surface of a substrate, a chemical action caused by components other than the abrasive grains on the surface of the substrate, or a combination of these. Therefore, the shape and type of the abrasive grains have a large effect on the polishing rate.

[0013] The polishing composition of the present invention is an abrasive having a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2The polishing composition contains silica particles having the following properties (hereinafter, also referred to as "silica particles having a low silanol group density"). Polycrystalline silicon has high hydrophobicity, and generally, the lower the silanol group density of the abrasive grains, the more hydrophobic they are and the easier they are to approach a hydrophobic object to be polished. Therefore, during polishing, the silica particles having a low silanol group density contained in the polishing composition approach the polycrystalline silicon film, which is the object to be polished, and can sufficiently apply mechanical force to the surface (polishing surface) of the polycrystalline silicon film, thereby enabling suitable polishing.

[0014] The polishing composition of the present invention has an electrical conductivity of 0.5 mS / cm or more and 10 mS / cm or less, and a pH of 10 or more and 12 or less. In general, the polishing rate of a silicon oxide film is increased by making the composition alkaline, but the selectivity of the polishing rate of a polycrystalline silicon film is likely to decrease. In the present invention, it is required to increase the selectivity of the polishing rate of a polycrystalline silicon film, so that the polishing rate of a polycrystalline silicon film and the polishing rate of a silicon oxide film need to be balanced. In the present invention, if the electrical conductivity of the polishing composition is 0.5 mS / cm or more and 10 mS / cm or less, the electrostatic repulsion between the abrasive grains and the silicon oxide film (e.g., a TEOS film) is suppressed by the compression of the electric double layer, and the two are easily brought close to each other, which is considered to facilitate polishing. If the pH of the polishing composition is 10 or more and 12 or less, the surface of the polycrystalline silicon film can be etched and embrittled, so that the polycrystalline silicon film can be easily polished. From the above, it can be said that the present invention provides a novel polishing composition that can efficiently polish silicon oxide films by virtue of having specific ranges of electrical conductivity and pH, and that has silica particles with a low silanol group density that approach polycrystalline silicon films and contribute to polishing the polycrystalline silicon film.

[0015] [Polished object] The object to be polished according to the present invention includes a polycrystalline silicon (polysilicon) film and a silicon oxide film. That is, the object to be polished according to the present invention is used for polishing an object to be polished that includes a polycrystalline silicon film and a silicon oxide film.

[0016] Examples of silicon oxide films include TEOS (Tetraethyl Orthosilicate) type silicon oxide films (hereinafter simply referred to as "TEOS films") produced using tetraethyl orthosilicate as a precursor, HDP (High Density Plasma) films, USG (Undoped Silicate Glass) films, PSG (Phosphorus Silicate Glass) films, BPSG (Boron-Phospho Silicate Glass) films, and RTO (Rapid Thermal Oxidation) films.

[0017] The object to be polished according to the present invention may contain other materials in addition to the polycrystalline silicon (polysilicon) film and the silicon oxide film, such as silicon nitride (SiN), silicon carbonitride (SiCN), amorphous silicon, metal, and SiGe.

[0018] Examples of the metal include tungsten, copper, aluminum, cobalt, hafnium, nickel, gold, silver, platinum, palladium, rhodium, ruthenium, iridium, and osmium.

[0019] [Abrasive grain] The polishing composition of the present invention contains abrasive grains. In the polishing composition of the present invention, the abrasive grains have a silanol group density of 0 particles / nm 2 More than 4 pieces / nm 2 In one embodiment, the abrasive grains include silica particles having a silanol group density of 0 / nm 2 More than 4 pieces / nm 2 The silica particles are composed of the following: In this specification, "silanol group density" means the number of silanol groups per unit area of ​​the silica particle surface. The silanol group density is an index for expressing the electrical or chemical properties of the silica particle surface.

[0020] In this specification, the silanol group density is calculated based on the specific surface area measured by the BET method and the amount of silanol groups measured by titration. For example, the average silanol group density (unit: silanol group / nm2) on the surface of silica (polishing grain) was determined by the Sears titration method using neutralization titration described in "Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983" by GW Sears. 2 ) can be calculated. The "Sears titration method" is an analytical method commonly used by colloidal silica manufacturers to evaluate silanol group density, and is a calculation method based on the amount of sodium hydroxide solution required to change the pH from 4 to 9. Details of silanol group density measurement are described in detail in the Examples below.

[0021] In one embodiment of the present invention, the number of silanol groups per unit surface area of ​​the abrasive grain is set to 0 / nm 2 More than 4 pieces / nm 2 In order to achieve the above, it is effective to select a manufacturing method for the abrasive grains, and for example, it is preferable to carry out a heat treatment such as calcination. In one embodiment of the present invention, calcination is carried out, for example, by holding the abrasive grains (e.g., silica) in an environment of 120 to 200°C for 30 minutes or more. By carrying out such a heat treatment, the number of silanol groups on the abrasive grain surface can be reduced to 0 groups / nm 2 More than 4 pieces / nm 2 Therefore, in the present invention, by subjecting the abrasive grains to such a special treatment, the number of silanol groups on the abrasive grain surface can be reduced to a desired value such as 0 / nm2 or less. 2 More than 4 pieces / nm 2 It can be as follows:

[0022] In one embodiment, the silanol group density of the silica particles is 0 / nm 2 More than 4 pieces / nm 2 The silanol group density of the silica particles is preferably 0.5 / nm 2 More than 4 pieces / nm 2 More preferably, it is 0.6 particles / nm 2More than 3.8 pieces / nm 2 More preferably, the number is 0.8 / nm 2 More than 3.6 pieces / nm 2 or less, and particularly preferably 0.9 particles / nm 2 More than 3.5 pieces / nm 2 or less, and most preferably 1 / nm 2 More than 3 pieces / nm 2 When the silanol group density of the silica particles is within the above range, the silica particles can approach the polycrystalline silicon film during polishing, and the mechanical force of the silica particles can be effectively applied to the polycrystalline silicon film.

[0023] Silica particles are preferably colloidal silica.Methods for producing colloidal silica include sodium silicate method and sol-gel method, and the colloidal silica produced by any method can be suitably used as the silica particles of the present invention.However, from the viewpoint of reducing metal impurities, the colloidal silica produced by the sol-gel method is preferred, which can produce high purity.

[0024] Furthermore, the silica particles may be surface-modified as long as the silanol group density satisfies the above range. For example, the silica particles may be colloidal silica with an organic acid fixed thereto. The organic acid is fixed to the surface of the colloidal silica contained in the polishing composition by, for example, chemically bonding the functional group of the organic acid to the surface of the colloidal silica. The organic acid is not fixed to the colloidal silica by simply allowing the colloidal silica and the organic acid to coexist. If sulfonic acid, which is a type of organic acid, is to be fixed to the colloidal silica, it can be performed by, for example, the method described in “Sulfonic acid-functionalized silica through quantitative oxidation of thiol groups”, Chem. Commun. 246-247 (2003). Specifically, a silane coupling agent having a thiol group such as 3-mercaptopropyltrimethoxysilane is coupled to the colloidal silica, and then the thiol group is oxidized with hydrogen peroxide, thereby obtaining colloidal silica with a sulfonic acid fixed to the surface. Alternatively, when a carboxylic acid is immobilized on colloidal silica, it can be carried out by, for example, the method described in “Novel Silane Coupling Agents Containing a Photolabile 2-Nitrobenzyl Ester for Introduction of a Carboxy Group on the Surface of Silica Gel”, Chemistry Letters, 3, 228-229 (2000). Specifically, a silane coupling agent containing a photoreactive 2-nitrobenzyl ester is coupled to colloidal silica, and then the resulting mixture is irradiated with light to obtain colloidal silica having a carboxylic acid immobilized on the surface.

[0025] In the polishing composition of the present invention, the abrasive grains have a silanol group count of 0 / nm 2 More than 4 pieces / nm 2The polishing composition of the present invention may contain abrasive grains other than silica particles (hereinafter, other abrasive grains) having a silanol group number of 0 / nm or less. The type of other abrasive grains contained in the polishing composition of the present invention is not particularly limited, and examples thereof include abrasive grains having a silanol group number of 0 / nm or less. 2 More than 4 pieces / nm 2 Examples of the other abrasive grains include oxides of silica, alumina, zirconia, titania, etc., other than the silica particles described below. The other abrasive grains can be used alone or in combination of two or more. The other abrasive grains can be either commercially available products or synthetic products.

[0026] In the following description, when the term "abrasive grains" is used, that is, when the term "silica particles" is used, the number of silanol groups is 0 / nm2 unless otherwise specified. 2 More than 4 pieces / nm 2 Hereinafter, the term will refer to silica particles and other abrasive grains without distinction.

[0027] In the polishing composition of the present invention, the silica particles preferably have a negative zeta potential. Here, the "zeta (ζ) potential" refers to the potential difference that occurs at the interface between a solid and a liquid in contact with each other when they undergo relative motion. In the polishing composition of the present invention, the abrasive grains have a negative charge, so that the polishing speed of the polishing object can be improved. The zeta potential of the silica particles is preferably -80 mV or more and -10 mV or less, more preferably -70 mV or more and -15 mV or less, even more preferably -65 mV or more and -20 mV or less, and particularly preferably -60 mV or more and -25 mV or less. When the silica particles have a zeta potential in such a range, the desired effect of the present invention can be efficiently achieved.

[0028] The zeta potential of the abrasive grains in the polishing composition is calculated by subjecting the polishing composition to an ELS-Z2 manufactured by Otsuka Electronics Co., Ltd., measuring the composition at a measurement temperature of 25°C using a flow cell by the laser Doppler method (electrophoretic light scattering measurement method), and analyzing the obtained data using the Smoluchowski formula.

[0029] The lower limit of the average primary particle size of silica particles is preferably 5 nm or more, more preferably 7 nm or more, even more preferably 10 nm or more, particularly preferably 15 nm or more, and most preferably 20 nm or more.The upper limit of the average primary particle size of silica particles is preferably 300 nm or less, more preferably 250 nm or less, even more preferably 200 nm or less, particularly preferably 180 nm or less, and most preferably 150 nm or less.Within such a range, the desired effect of the present invention can be efficiently achieved.

[0030] The average primary particle size of the abrasive grains can be calculated based on the specific surface area measured using the BET method.

[0031] The lower limit of the average secondary particle diameter of silica particles is preferably 10 nm or more, more preferably 20 nm or more, even more preferably 30 nm or more, particularly preferably 40 nm or more, and most preferably 50 nm or more. The upper limit of the average secondary particle diameter of silica particles is preferably 200 nm or less, more preferably 180 nm or less, even more preferably 150 nm or less, particularly preferably 100 nm or less, and most preferably 80 nm or less. That is, the average secondary particle diameter of silica particles is preferably 10 nm or more and 200 nm or less, more preferably 20 nm or more and 180 nm or less, even more preferably 30 nm or more and 150 nm or less, particularly preferably 40 nm or more and 100 nm or less, and most preferably 10 nm or more and 250 nm or less. Within such a range, the desired effect of the present invention can be efficiently achieved.

[0032] The average secondary particle diameter of the abrasive grains can be measured, for example, by a dynamic light scattering method such as a laser diffraction scattering method. That is, the average secondary particle diameter of the abrasive grains corresponds to the diameter D50 of the particles when the cumulative particle mass from the fine particle side reaches 50% of the total particle mass in the particle size distribution of the abrasive grains determined by the laser diffraction scattering method.

[0033] The average degree of association of the abrasive grains is preferably 4.0 or less, more preferably 3.0 or less, and even more preferably 2.5 or less. As the average degree of association of the abrasive grains decreases, the occurrence of defects on the surface of the object to be polished can be further reduced. In addition, the average degree of association of the abrasive grains is preferably 1.5 or more, more preferably 1.8 or more. As the average degree of association of the abrasive grains increases, there is an advantage that the polishing rate by the polishing composition improves. The average degree of association of the abrasive grains is obtained by dividing the value of the average secondary particle diameter of the abrasive grains by the value of the average primary particle diameter.

[0034] The size of the abrasive grains (average primary particle size, average secondary particle size, etc.) can be appropriately controlled by selecting the manufacturing method of the abrasive grains, etc.

[0035] The lower limit of the content (concentration) of the abrasive grains in the polishing composition according to one embodiment of the present invention is preferably 0.2 mass% or more, more preferably 0.3 mass% or more, and even more preferably 0.5 mass% or more, based on the polishing composition. The upper limit of the content of the abrasive grains in the polishing composition according to the present invention is preferably 20 mass% or less, more preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less, based on the polishing composition. In such a range, the polishing rate can be further improved. In addition, when the polishing composition contains two or more kinds of abrasive grains, the content of the abrasive grains means the total amount of these.

[0036] [Alkaline compounds] In one embodiment, the polishing composition of the present invention contains an alkali compound. The alkali compound has the effect of adjusting the pH and the electrical conductivity in the polishing composition of the present invention. Examples of the alkali compound include hydroxides of alkali metals such as sodium hydroxide and potassium hydroxide; carbonates such as sodium carbonate and potassium carbonate; amines such as ethylenediamine, diglycolamine, piperazine, and aminoethylpiperazine; and ammonia. The alkali compounds can be used alone or in combination of two or more. By using these alkali compounds, the pH can be adjusted to an alkaline range in which polycrystalline silicon and silicon oxide contained in the polishing object are easily dissolved. In addition, by using these alkali compounds, the electrical conductivity of the polishing composition can be adjusted to a range that compresses the electric double layer generated at the interface between the abrasive grains and the wafer (polycrystalline silicon film or silicon oxide film) and reduces the area where electrostatic repulsion between the two begins to occur. This makes it easier for the abrasive grains to approach the wafer, thereby improving the polishing speed. Since the alkali compound is hardly adsorbed to the abrasive grain surface or the surface of the object to be polished during polishing, and most of it is dissolved in the dispersion medium, it hardly or does not hinder the polishing of the polycrystalline silicon film and the silicon oxide film. Therefore, the polishing composition containing the alkali compound according to the present invention can realize efficient polishing, and the expected effect of the present invention can be efficiently achieved.

[0037] In the present invention, from the viewpoint of pH adjustment and electrical conductivity adjustment, it is preferable to use potassium hydroxide as the alkaline compound. Also, from the viewpoint of electrical conductivity, it is preferable to include potassium carbonate as the alkaline compound. From the viewpoint of polishing rate, it is preferable to include diglycolamine, aminoethylpiperazine, and ammonia as the alkaline compound. Therefore, in a preferred embodiment, it is preferable to include one or more types selected from the group consisting of potassium carbonate, diglycolamine, aminoethylpiperazine, and ammonia as the alkaline compound.

[0038] Furthermore, by including one or more types selected from the group consisting of diglycolamine, aminoethylpiperazine, and ammonia as the alkaline compound, the polishing speed for the polycrystalline silicon film and the silicon oxide film can be further improved.

[0039] In one embodiment, the alkaline compound is one or more selected from the group consisting of potassium hydroxide, potassium carbonate, diglycolamine, aminoethylpiperazine, and ammonia. In one embodiment, the alkaline compound includes potassium hydroxide and one or more selected from the group consisting of potassium carbonate, diglycolamine, aminoethylpiperazine, and ammonia. In one embodiment, the alkaline compound includes potassium hydroxide and one or more selected from the group consisting of aminoethylpiperazine and diglycolamine. By including such an alkaline compound in the polishing composition, the expected effect of the present invention can be efficiently achieved.

[0040] The content (concentration) of the alkali compound is not particularly limited, and the content can be adjusted appropriately so that the polishing composition has a desired pH and electrical conductivity.For example, the content of the alkali compound is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and even more preferably 0.15 mass% or more, based on the total mass of the polishing composition.In addition, the upper limit of the content of the alkali compound is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 2 mass% or less, based on the total mass of the polishing composition.In addition, when the polishing composition contains two or more kinds of alkali compounds, the content of the alkali compound refers to the total amount of these.

[0041] [Electrical conductivity] The electrical conductivity of the polishing composition of the present invention is 0.5 mS / cm or more and 10 mS / cm or less. In one embodiment, the electrical conductivity of the polishing composition of the present invention is 3 mS / cm or more and 8 mS / cm or less. If the electrical conductivity of the polishing composition is less than 0.5 mS / cm, the electric double layer generated at the interface between the abrasive grains and the wafer (polycrystalline silicon film or silicon oxide film) becomes large, and the range in which electrostatic repulsion occurs becomes wider. This increases the total electrostatic repulsion, making it difficult for the abrasive grains to approach the wafer, and the polishing rate decreases. On the other hand, if the electrical conductivity of the polishing composition exceeds 10 mS / cm, the electrostatic repulsion between the abrasive grains becomes small, causing the abrasive grains to aggregate, resulting in problems with storage stability.

[0042] The lower limit of the electrical conductivity of the polishing composition is preferably 1 mS / cm or more, more preferably 2 mS / cm or more, even more preferably 3 mS / cm or more, particularly preferably 4 mS / cm or more, and most preferably 4.5 mS / cm or more. The upper limit of the electrical conductivity of the polishing composition of the present invention is preferably 9 mS / cm or less, more preferably 8 mS / cm or less, even more preferably 7.5 mS / cm or less, particularly preferably 7 mS / cm or less, and most preferably 6 mS / cm or less. That is, the electrical conductivity of the polishing composition of the present invention is preferably 1 mS / cm or more and 9 mS / cm or less, more preferably 2 mS / cm or more and 8 mS / cm or less, even more preferably 3 mS / cm or more and 7.5 mS / cm or less, particularly preferably 4 mS / cm or more and 7 mS / cm or less, and most preferably 4.5 mS / cm or more and 6 mS / cm or less. When the electrical conductivity of the polishing composition is in the above range, the desired effect of the present invention can be efficiently achieved. The electrical conductivity of the polishing composition is a value measured by a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71).

[0043] [pH and pH adjusters] The pH of the polishing composition of the present invention is 10 or more and 12 or less. If the pH of the polishing composition is less than 10, the polishing rate of the polycrystalline silicon film and silicon oxide film, which are the objects to be polished, cannot be improved, and the expected effect of the present invention is not achieved. The pH of the polishing composition of the present invention may be 10 or more, but is preferably pH 10.5 or more, more preferably pH 10.9 or more, even more preferably pH 11 or more, even more preferably pH 11 or more, particularly preferably pH 11.1 or more, and most preferably pH 11.2 or more. If the pH of the polishing composition exceeds 12, overpolishing occurs with respect to the polycrystalline silicon film and silicon oxide film, which are the objects to be polished, and the selectivity of the polishing rate of the polycrystalline silicon film decreases. The pH of the polishing composition of the present invention may be 12 or less, but is preferably less than pH 12, more preferably pH 11.9 or less, even more preferably pH 11.9 or less, even more preferably pH 11.8 or less, particularly preferably pH 11.7 or less, and most preferably pH 11.6 or less.

[0044] The pH of the polishing composition can be measured by, for example, a pH meter.Specifically, using a pH meter (for example, Horiba, Ltd., model number: LAQUA) or the like, perform three-point calibration using standard buffer (phthalate pH buffer pH: 4.01 (25°C), neutral phosphate pH buffer pH: 6.86 (25°C), carbonate pH buffer pH: 10.01 (25°C)), then put a glass electrode into the polishing composition, and measure the value after 2 minutes or more have passed and the pH of the polishing composition is stabilized.

[0045] The polishing composition of the present invention contains abrasive grains, an alkaline compound, and a dispersing medium as essential components, but if it is difficult to obtain the desired pH using these alone, the pH may be adjusted by adding a pH adjuster within a range that does not impair the effects of the present invention.

[0046] The pH adjuster may be a base other than the above-mentioned alkaline compounds, an inorganic acid, or an organic acid, and these may be used alone or in combination of two or more kinds.

[0047] Specific examples of bases that can be used as pH adjusters include compounds other than the above-mentioned alkaline compounds, such as quaternary ammonium hydroxide or a salt thereof. Specific examples of salts include sulfates, acetates, etc.

[0048] Specific examples of inorganic acids that can be used as pH adjusters include hydrochloric acid, sulfuric acid, nitric acid, hydrofluoric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid. Among these, hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid are preferred.

[0049] Specific examples of organic acids that can be used as pH adjusters include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, n-hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylpentanoic acid, n-heptanoic acid, 2-methylhexanoic acid, n-octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, lactic acid, diglycolic acid, 2-furan carboxylic acid, 2,5-furandicarboxylic acid, 3-furan carboxylic acid, 2-tetrahydrofuran carboxylic acid, methoxyacetic acid, methoxyphenylacetic acid, and phenoxyacetic acid. Organic sulfuric acids such as methanesulfonic acid, ethanesulfonic acid, and isethionic acid may also be used. Among these, dicarboxylic acids such as malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid and tartaric acid, and tricarboxylic acids such as citric acid are preferred.

[0050] Instead of or in combination with an inorganic or organic acid, a salt such as an alkali metal salt of an inorganic or organic acid may be used as a pH adjuster. In the case of a combination of a weak acid and a strong base, a strong acid and a weak base, or a weak acid and a weak base, a pH buffering effect can be expected.

[0051] The amount of the pH adjuster added is not particularly limited, and may be appropriately adjusted so that the polishing composition has a desired pH.

[0052] [Dispersion medium] The polishing composition of the present invention contains a dispersion medium for dispersing each component. Examples of the dispersion medium include water; alcohols such as methanol, ethanol, and ethylene glycol; ketones such as acetone, and mixtures thereof. Of these, water is preferred as the dispersion medium. That is, according to a preferred embodiment of the present invention, the dispersion medium contains water. According to a more preferred embodiment of the present invention, the dispersion medium is substantially composed of water. Note that the above "substantially" means that a dispersion medium other than water may be included as long as the objective effect of the present invention can be achieved, and more specifically, the dispersion medium is preferably composed of 90% by mass or more and 100% by mass or less of water and 0% by mass or more and 10% by mass or less of a dispersion medium other than water, and more preferably composed of 99% by mass or more and 100% by mass or less of water and 0% by mass or more and 1% by mass or less of a dispersion medium other than water. Most preferably, the dispersion medium is water.

[0053] From the viewpoint of not inhibiting the action of the components contained in the polishing composition, it is preferable for the dispersion medium to be water that contains as few impurities as possible. Specifically, pure water or ultrapure water from which impurity ions have been removed with an ion exchange resin and then foreign matter has been removed through a filter, or distilled water is more preferable.

[0054] [Other ingredients] The polishing composition of the present invention may further contain known additives that can be used in polishing compositions, such as complexing agents, preservatives, and fungicides, as necessary, within the scope of not significantly impairing the effects of the present invention. However, according to an embodiment of the present invention, the polishing composition does not substantially contain an oxidizing agent. According to such an embodiment, even when a polishing target containing a polycrystalline silicon film and a silicon oxide film (preferably a TEOS film) is polished, the polycrystalline silicon film and the silicon oxide film can be polished at a high polishing rate, and the selectivity of the polishing rate of the polycrystalline silicon film (the ratio of the polishing rate of the polycrystalline silicon film to the polishing rate of the silicon oxide film) is high. Note that "substantially free" includes the concept of not being contained at all in the polishing composition, as well as the case where the polishing composition contains 0.1 mass % or less.

[0055] [Method of manufacturing the polishing composition] The method for producing the polishing composition of the present invention is not particularly limited, and can be obtained, for example, by stirring and mixing abrasive grains and other components as necessary in a dispersion medium (for example, water). The details of each component are as described above.

[0056] The temperature at which the components are mixed is not particularly limited, but is preferably 10° C. to 40° C. Heating may be performed to increase the dissolution rate. The mixing time is also not particularly limited as long as the components can be mixed uniformly.

[0057] [Polishing method and semiconductor substrate manufacturing method] As described above, the polishing composition of the present invention is suitable for use in polishing an object to be polished that includes a polycrystalline silicon film and a silicon oxide film. Thus, the present invention provides a polishing method for polishing an object to be polished that includes a polycrystalline silicon film and a silicon oxide film with the polishing composition of the present invention. That is, the present invention includes a polishing method comprising a step of polishing an object to be polished that includes a polycrystalline silicon film and a silicon oxide film with the polishing composition of the present invention. The present invention also provides a method for producing a semiconductor substrate, comprising a step of polishing a semiconductor substrate that includes a polycrystalline silicon film and a silicon oxide film by the polishing method.

[0058] As a polishing device, a general polishing device can be used which is equipped with a holder for holding a substrate or the like having an object to be polished, a motor whose rotation speed can be changed, and a polishing platen onto which a polishing pad (polishing cloth) can be attached.

[0059] The polishing pad may be made of any material, including, without particular limitation, a general nonwoven fabric, polyurethane, porous fluororesin, etc. The polishing pad is preferably provided with grooves for storing the polishing liquid.

[0060] Regarding the polishing conditions, for example, the rotation speed of the polishing platen was 10 rpm (0.17 s -1 ) or more 500rpm(8.3s -1 ) or less. The pressure (polishing pressure) applied to the substrate having the object to be polished is preferably 0.5 psi (3.4 kPa) or more and 10 psi (68.9 kPa) or less. The method of supplying the polishing composition to the polishing pad is not particularly limited, and for example, a method of continuously supplying the composition using a pump or the like is used. There is no limit to the amount of supply, but it is preferable that the surface of the polishing pad is always covered with the polishing composition of the present invention.

[0061] After polishing, the substrate is washed with running water, and water droplets adhering to the substrate are removed by a spin dryer or the like, followed by drying to obtain a substrate having a metal-containing layer.

[0062] The polishing composition of the present invention may be a one-liquid type or a multi-liquid type such as a two-liquid type. The polishing composition of the present invention may be prepared by diluting the stock solution of the polishing composition, for example, 10 times or more, with a diluent such as water.

[0063] [Method for polishing polycrystalline silicon film and silicon oxide film at high polishing rates while increasing the selectivity of the polishing rate of the polycrystalline silicon film] According to the present invention, a method is provided that can polish a polycrystalline silicon film and a silicon oxide film at a high polishing rate and can increase the selectivity of the polishing rate of polycrystalline silicon. The specific description of the polishing composition is as described above.

[0064] [Polishing speed] In the present invention, the polishing speed of the polycrystalline silicon film is preferably 2000 Å / min to 7000 Å / min, more preferably 2200 Å / min to 6800 Å / min, even more preferably 2500 Å / min to 6500 Å / min, and particularly preferably 3000 Å / min to 6000 Å / min. The polishing speed of the silicon oxide film (TEOS film) is preferably 35 Å / min to 500 Å / min, more preferably 50 Å / min to 300 Å / min, even more preferably 80 Å / min to 250 Å / min, and particularly preferably 100 Å / min to 200 Å / min.

[0065] [Selection ratio] The selectivity is calculated by dividing the polishing speed (Å / min) of a polycrystalline silicon film (poly-Si) by the polishing speed (Å / min) of a silicon oxide film (TEOS). In the present invention, the selectivity (poly-Si / TEOS) is preferably 10 or more and 50 or more, more preferably 11 or more and 45 or less, and even more preferably 15 or more and 40 or more. EXAMPLES

[0066] The present invention will be described in more detail using the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. Unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively. In the following examples, unless otherwise specified, the operations were performed under the conditions of room temperature (20 to 25°C) / relative humidity 40 to 50% RH.

[0067] [Preparation of abrasive grains] (Preparation of Silica Particles) As the silica particles, silica particles having the silanol group density shown in Table 1 were prepared. That is, the silica particles are calcined by, for example, holding the silica in an environment of 120 to 200° C. for 30 minutes or more, so that the number of silanol groups on the silica particle surface is reduced to 0 / nm2 More than 4 pieces / nm 2 The values ​​were adjusted to the desired values, such as: Silica particle A: silanol group density 1.6 / nm 2 , average primary particle size: 30nm, average secondary particle size: 70nm, average degree of association: 2.3 Silica particle B: silanol group density 3.5 / nm 2 , average primary particle size: 30nm, average secondary particle size: 70nm, average degree of association: 2.3 Silica particle C: silanol group density 5.7 particles / nm 2 , average primary particle size: 35 nm, average secondary particle size: 70 nm, average degree of association: 2 The silanol group density of the silica particles (unit: particles / nm 2 ) was calculated by the following method after measuring and calculating each parameter by the following measurement and calculation methods.

[0068] [Calculation method for silanol group density] The silanol group density of the silica particles was calculated by the Sears method using neutralization titration described in Analytical Chemistry, vol. 28, No. 12, 1956, 1982-1983 by GW Sears.

[0069] More specifically, the silanol group density of the silica particles was calculated by the following formula 1, using each of the silica particles as a measurement sample and titrating it by the above-mentioned method.

[0070] ρ = (c × V × N A ×10 -21 ) / (C×S)...Equation 1 In the above formula 1, ρ is the silanol group density (pcs / nm 2 ) ; c represents the concentration (mol / L) of the sodium hydroxide solution used in the titration; V represents the volume (L) of sodium hydroxide solution required to raise the pH from 4.0 to 9.0; N A represents the Avogadro constant (units / mol); S represents the BET specific surface area (nm / g) of the silica particles.

[0071] [Silica particle size] The average primary particle size of the abrasive grains (silica particles) was calculated from the specific surface area of ​​the abrasive grains measured by the BET method using a Micromeritics "Flow SorbII 2300" and the density of the abrasive grains. The average secondary particle size of the abrasive grains (silica particles) was measured using a Nikkiso Co., Ltd. dynamic light scattering particle size and particle size distribution analyzer UPA-UTI151.

[0072] [Preparation of polishing composition] Example 1 The silica particles a obtained above (silanol group density 1.6 / nm 2 A mixture was obtained by adding 2 mass% of 2,000 sucrose as an alkaline compound and 0.1 mass% of aminoethylpiperazine as an alkaline compound to pure water as a dispersion medium at room temperature (25°C) to obtain a final concentration of 2,000 sucrose as an alkaline compound and 0.1 mass% of aminoethylpiperazine as an alkaline compound.

[0073] Thereafter, in order to adjust the pH, potassium hydroxide was added as an alkaline compound to the mixture so that the pH was 11.3, and the mixture was stirred and mixed at room temperature (25° C.) for 30 minutes to prepare a polishing composition. The pH of the polishing composition (liquid temperature: 25° C.) was confirmed with a pH meter (manufactured by Horiba Ltd., model number: LAQUA).

[0074] [Silica particle size] The particle sizes (average primary particle size, average secondary particle size) of the abrasive grains in the obtained polishing composition were the same as those of the powdered abrasive grains. The particle size was measured by the same method as described above.

[0075] [Zeta potential] The zeta potential of the abrasive grains (silica particles) in the polishing composition was measured using a zeta potential measuring device manufactured by Otsuka Electronics Co., Ltd. (device name "ELS-Z2").

[0076] [Electrical Conductivity] The electrical conductivity (unit: mS / cm) of the polishing composition (liquid temperature: 25° C.) was measured using a tabletop electrical conductivity meter (manufactured by Horiba, Ltd., model number: DS-71).

[0077] (Examples 2 to 9, Comparative Examples 1 to 3) Polishing compositions of Examples 2 to 9 and Comparative Examples 1 to 3 were prepared in the same manner as in Example 1, except that the type of silica particles and the type and content (pH and electrical conductivity) of the alkaline compound were changed as shown in Table 1 below. In Table 1 below, "-" indicates that the agent was not contained. The pH and electrical conductivity of each obtained polishing composition, the average secondary particle size and zeta potential of the abrasive grains (silica particles) in each polishing composition are shown in Table 1 below. The particle sizes (average primary particle size, average secondary particle size) of the abrasive grains in the obtained polishing composition were similar to those of the powdered abrasive grains.

[0078] In Table 1, the "particle size" for silica particles represents the average secondary particle size, while in the column for alkaline compounds, "AEP" represents aminoethylpiperazine, "DGA" represents diglycolamine, and "EC" represents electrical conductivity. In the column for polishing speed, "poly-Si" represents a polycrystalline silicon film. In the column for selectivity, "poly-Si / TEOS" represents the selectivity of a polycrystalline silicon film relative to a TEOS film, and is calculated by dividing the polishing speed for a polycrystalline silicon film by the polishing speed for a TEOS film.

[0079] [Evaluation of polishing speed] Each of the polishing compositions obtained above was used to measure the removal rate when polishing the following object to be polished under the following polishing conditions.

[0080] (Polishing equipment and polishing conditions) Polishing equipment: Engis Japan Co., Ltd. Lapping machine EJ-380IN-CH Polishing pad: Nitta DuPont hard polyurethane pad IC1010 Polishing pressure: 3.0 psi (1 psi = 6894.76 Pa) Polishing platen rotation speed: 60 rpm Head (carrier) rotation speed: 60 rpm Supply of polishing composition: free-flowing Polishing composition supply amount: 100mL / min Polishing time: 60 seconds.

[0081] (Object to be polished) A 300 mm blanket wafer with a 5000 Å thick polycrystalline silicon film on its surface was prepared as the polishing target. A silicon wafer (300 mm, blanket wafer, manufactured by Advantec Co., Ltd.) with a 500 Å thick TEOS film formed on its surface was also prepared as the polishing target. The wafer was then cut into 30 mm x 30 mm chips to create coupons, which were used as test pieces for polishing tests. Details of the polishing target used in the test are shown below.

[0082] (polishing speed) The removal rate (RR) was calculated according to the following formula.

[0083]

number

[0084] The film thickness was measured using an optical interference type film thickness measuring device (manufactured by Dainippon Screen Mfg. Co., Ltd., model number: Lambda Ace VM-2030), and the polishing rate was evaluated by dividing the difference in film thickness before and after polishing by the polishing time.

[0085] The evaluation results of the polishing rates for the polycrystalline silicon film and the TEOS film are shown in Table 1 below.

[0086] [Table 1]

[0087] As shown in Table 1, when the polishing compositions of Examples 1 to 9 were used, the polishing rate for the polycrystalline silicon film exceeded 2000 Å / min, and the polishing rate for the TEOS film was 100 Å / min or more, indicating that polishing could be performed at a higher polishing rate than the polishing compositions of Comparative Examples 1 to 3. Furthermore, when the polishing compositions of Examples 1 to 9 were used, the selectivity of the polishing rate for the polycrystalline silicon film was 10 or more and 50 or less, indicating that the polycrystalline silicon film and the TEOS film could be polished at a high polishing rate, and the polycrystalline silicon film could be polished at a high selectivity.

[0088] This shows that the polishing composition has a specific range of pH and electrical conductivity, and contains silica particles having a specific silanol group density, so that it is possible to polish polycrystalline silicon films and TEOS films at a high polishing rate and to polish polycrystalline silicon films with a high selectivity.

Claims

1. A polishing composition comprising an abrasive grain, an alkali compound, and a dispersion medium, The abrasive grains have a silanol group density of 0 / nm 2 More than 4 / nm 2 Silica particles comprising: The alkaline compound includes potassium hydroxide and one or more compounds selected from the group consisting of diglycolamine and aminoethylpiperazine, The electrical conductivity is 0.5 mS / cm or more and 10 mS / cm or less, A polishing composition having a pH of 10 or more and 12 or less.

2. The silanol group density of the silica particles is 0 / nm 2 More than 2 / nm 2 2. The polishing composition according to claim 1, wherein:

3. 3. The polishing composition according to claim 1, wherein the electrical conductivity is 3 mS / cm or more and 8 mS / cm or less.

4. The polishing composition according to any one of claims 1 to 3, having a pH of more than 11.

5. The polishing composition according to any one of claims 1 to 4, which is substantially free of an oxidizing agent.

6. The polishing composition according to any one of claims 1 to 5, which is used for polishing an object to be polished, which includes a polycrystalline silicon film and a silicon oxide film.

7. 7. A polishing method comprising a step of polishing an object containing a polycrystalline silicon film and a silicon oxide film with the polishing composition according to claim 1.

8. A method for producing a semiconductor substrate, comprising a step of polishing a semiconductor substrate including a polycrystalline silicon film and a silicon oxide film by the polishing method according to claim 7.

Citation Information

Patent Citations

  • Aqueous dispersion for chemical mechanical polishing and chemical mechanical polishing method using the same

    JP2013041992A

  • Composition for polishing

    JP2016149402A

  • Polishing composition

    JP2019165226A

  • Chemical mechanical polishing of alumina

    US20160032461A1

  • Composition and method for polysilicon cmp

    WO2021046080A1